2017
DOI: 10.1093/infdis/jiw570
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the Administration of Multiple Injectable Vaccines in a Single Immunization Visit in Albania

Abstract: Background.Albania introduced inactivated polio vaccine (IPV) into its immunization system in May 2014, increasing the maximum recommended number of injectable vaccines given in a single visit from 2 to 3.Methods.Health-care providers and caregivers were interviewed at 42 health facilities in Albania to assess knowledge, attitudes, and practices regarding injectable vaccine administration. Immunization register data were abstracted from December 2014 to July 2015 at the same facilities to explore the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
2
6
0
1
Order By: Relevance
“…However, relevant studies from developing countries are lacking [ 9 ]. Our results from the Philippines, a populous lower-middle income country in Asia, were comparable to recently published assessments in other low and middle income countries [ 10 , 14 , 15 ] We observed HCPs and caregivers to be receptive to multiple injections, with acceptance increasing after HCPs and caregivers had experience with this practice. Furthermore, our study showed that attitudes do not always align with practices; for example, some caregivers stated that they were comfortable with their child receiving only 1–2 injections at a visit yet allowed their child to receive three.…”
Section: Discussionsupporting
confidence: 89%
“…However, relevant studies from developing countries are lacking [ 9 ]. Our results from the Philippines, a populous lower-middle income country in Asia, were comparable to recently published assessments in other low and middle income countries [ 10 , 14 , 15 ] We observed HCPs and caregivers to be receptive to multiple injections, with acceptance increasing after HCPs and caregivers had experience with this practice. Furthermore, our study showed that attitudes do not always align with practices; for example, some caregivers stated that they were comfortable with their child receiving only 1–2 injections at a visit yet allowed their child to receive three.…”
Section: Discussionsupporting
confidence: 89%
“…In the Gambia, all children with an immunization visit at 4 months of age received the recommended doses of IPV, PCV, and pentavalent vaccine when all 3 vaccines were in stock [ 42 ]. In Albania, 85% of children with immunization visits at 2 or 4 months of age received all of the recommended doses of IPV, PCV, and pentavalent vaccine at a single visit [ 43 ]. In these 2 cases and as previously found in South Africa, concerns about the addition of a new injectable vaccine dose for infants did not prevent high uptake of IPV, PCV, and pentavalent vaccine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of IPV in Uganda, like elsewhere, resulted in the delivery of multiple injections during a single visit, with infants receiving IPV alongside pentavalent vaccine (for diphtheria, tetanus and whole-cell pertussis; hepatitis B; Haemophilus influenza type b) and pneumococcal vaccine at 14 weeks ( Preza et al., 2017) . Infants also receive the third and final OPV dose at 14 weeks.…”
Section: Introductionmentioning
confidence: 99%